PENGARUH PENDEKATAN CONCRETE-PICTORIAL-ABSTRACT (CPA) BERBANTUAN AUGMENTED REALITY (AR) TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SD - Elisa Nur Azizah; Hafiziani Eka Putri; Puji Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low mathematical critical thinking skills of elementary school students. Mathematical critical thinking skills are critical for students to master. The purpose of this study was to determine and analyze the effect of the CPA approach assisted by AR on the mathematical critical thinking skills of elementary school students. The type of research used is a quasi-experiment with a non-equivalent control group design with the subject matter of geometry building space. This research was conducted on 42 students in one of the elementary schools in Purwakarta Regency. Data were collected before and after learning by giving test instruments of mathematical critical thinking skills of elementary school students and documentation. Data analysis techniques are done with descriptive and inferential analysis in the form of normality tests, homogeneity tests, and t' test. Based on the results of data analysis, it shows that there is an influence between the application of learning with the CPA approach assisted by AR on improving students' mathematical critical thinking skills by 81.3%. Thus, the CPA approach assisted by AR can be used as an alternative learning approach that can help improve the mathematical critical thinking skills of elementary school students.